Digital Tone Control Menggunakan Mikrokontroller 8-Bit - Turahyo turahyo (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2019)
AbstractThe quality of the audio sound system that is generated depends on the tone control. Good audio tone control signal output produces an audio signal that approaches the input audio signal. Tone controls are generally used on audio sound system devices using potentiometers as regulating devices. Potentiometers are done in charcoal powder which has varying and linear barriers. Problems that often arise in potentiometers in the form of quick wear due to frequent friction, the output of the tone control will produce a noise when the relationship between the powder charcoal and the sweeping lever is not well connected, and linearity will change if the potentiometer is dirty due to dust. Microcontroller is electronic equipment that can be programmed according to user need. With a collaboration push button, Multiplexer and Analog to digital converter (ADC), can be utilized instead of a potentiometer. Setting the potentiometer is done by pressing the digital control tune up / down button. Based on the testing of the tone control on the volume setting, the input signal has strengthened 6.02 dB. In the bass setting, a signal with a frequency of 100-1 khz is passed, while the frequency of 2.5 khz is muted. In the treble setting, the frequency passed is 2.5 khz to 16 khz.